PENDAPAT KH. SALIM MARUF TENTANG JUAL BELI DALAM RISALAH MUAMALAH - Azhari, Fathurrahman; Hatim, Adi; Hatim, Adi (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2016)
The study of KH. Salim Maruf thought about buying and selling is important to do because sometimes his thought is in contrast to other scholars opinion. For example, KH. Salim Maruf said that buying and selling done by a drunk person is valid/legal. However, if it is done by children under the permission of the guardians, according to KH.Salim Maruf, is not valid/legal. KH. Salim Maruf also found that buying and selling to people whose treasure is doubtful is makruh. In addition, he also noted that buying and selling sacrificial meat is haram, bay al-urbun, bay munabadzah and bay mulamasah, bayataini fi bayatin, bay malaqih. KH. Salim Maruf did not give the legal proposition on each of his thought published in the book of Risalah Muamalah while the law is said to be invalid or false is determined from the aspect of legal proposition, therefore, it is necessary to study and search of the arguments used in book.